Grzegorz Wasowski in Wonderland: a Translator and a Magician - Tabakowska, Elżbieta (Porównania, 2016)
The paper brings an analysis of the new Polish translation of Alice’s Adventures in Wonderland by Grzegorz Wasowski, published as Perypetie Alicji na Czarytorium. By defining the translation strategy followed by the translator and pointing to possible reasons for this choice and its consequences, the author enters into discussion with the translator. Wasowski claims that „it is not possible to do it better than the previous translators – but it is possible to do it differently”. This leads to the eternal question about limits of translation and to the conclusion that at the time when reading the text is considered as its interpretation (and hence a translation is a translation of an interpretation, and the reception of the translation is an interpretation of the interpretation) each new interpretation becomes a significant element of the translation series.